The Readiness of Wonosobo and Banjarnegara Towards Open Defecation Free Regencies - Sutopo Patria Jati; Nurhasmadiar Nandini; Nikie Astorina Yunita Dewanti; Nissa Kusariana; Bimastyaji Surya Ramadan; Budiyono Budiyono; Pangi Pangi; Vanessa Rizky Aditya (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Open defecation is defined as the practice of defecating in fields, forests, bushes, rivers, beaches, or other open areas, causing soil, water, and air contamination. This can cause environmental pollution and diseases (diarrhea and pneumonia, etc.). Banjarnegara and Wonosobo are the two districts with the lowest percentages of Open Defecation Free (ODF) in Central Java. This study aimed to determine the readiness of Banjarnegara and Wonosobo to become ODF regencies. Methods: This descriptive study used a qualitative approach. Data collection was conducted through Focus Group Discussions (FGD) with policy actors responsible for accelerating ODF in Wonosobo and Banjarnegara. Results and Discussion: This study found that Wonosobo and Banjarnegara were constrained by five issues: policies/regulations and strategies, institutional arrangements, financing, planning and monitoring, and capacity building. A situation analysis involving the Working Group on Housing and Settlement Areas (Pokja PKP) for Wonosobo and Banjarnegara found the ODF's main obstacles, namely coordination and commitment (supply), and community behavior (demand). Conlusion: The readiness of Wonosobo and Banjarnegara as ODF regencies needs to be reviewed, especially the commitment of regional leaders to institution-strengthening policies and public education.